Icariin against osteoporosis: a review of advances in molecular mechanisms to biomedical applications - Fu, Boyi; Yu, Shasha; Chen, Shengxiong; Hu, Bo (Frontiers in Pharmacology, 2025)
Osteoporosis (OP) is characterized by decreased bone mass and deterioration of bone microstructure, significantly increasing fracture risk. Icariin (ICA), a natural compound, has demonstrated efficacy in improving bone microstructure and bone mineral density (BMD) across multiple OP models, with its targeting efficacy enhanced through innovative drug delivery systems. This review systematically summarizes recent advances in ICA research, focusing on its application dosage forms, therapeutic performance in various animal models, and underlying molecular mechanisms. In order to ensure a comprehensive and reliable report, we conducted a systematic search in the core collection of web of science according to PRISMA guidelines, and finally included 182 publications for in-depth analysis. ICA’s therapeutic efficacy is enhanced through innovative delivery systems, including traditional Chinese medicine formulations and advanced biomaterials. Studies across postmenopausal, glucocorticoid-induced, aging, and diabetic OP models consistently demonstrate ICA’s ability to improve bone microarchitecture and BMD. Mechanistically, ICA exerts dual-regulation effects by promoting osteogenesis while inhibiting osteoclastogenesis, coupled with multi-target actions involving autophagy regulation, anti-inflammatory effects, iron overload mitigation, and oxidative stress reduction. In conclusion, ICA’s comprehensive and multi-mechanistic intervention strategy, augmented by advanced delivery systems, presents a natural, safe, and efficacious candidate for OP treatment. This review synthesizes critical advances from molecular mechanisms to biomedical applications, supporting further clinical translation of ICA-based therapies.